Phosphorus Fractionations and Availability in Areas under Different Management Systems in the Cerrado - José Luiz Rodrigues Torres; Danyllo Denner de Almeida Costa; Marcos Gervasio Pereira; Luiz Victorio França Guardieiro; Arcângelo Loss; Cledimar Rogério Lourenzi; Antônio Paz Gonzalez; Mychelle Carvalho; Dinamar Márcia da Silva Vieira (Agronomy, 2023)
The input of organic matter in the soil by the no-tillage system (NTS) increases as the system becomes established, raising the levels of organic phosphorus (P) and reducing the P soil adsorption. This study evaluated the availability of organic and inorganic P in areas under different management systems and stages of adoption in the Cerrado. The data were analyzed as a completely randomized design, corresponding to: (1) an NTS after 5 years of its implantation (NTS5); (2) an NTS after 17 years of its implantation (NTS17); (3) a conventional tillage system more than 20 years old (CTS); (4) Native Cerrado (NC). There were five repetitions for all treatments. Depths of 0–5 and 5–10 cm were evaluated for the available P (P-avail), remaining P (P-rem), organic P (oP), and inorganic P (iP) forms extracted with Sodium bicarbonate (NaHCO3) (P-avail), Sulfuric acid (H2SO4) (moderately labile), and Sodium hydroxide (NaOH) (moderately resistant). The P from the sequential extractions accumulated at a depth of 0–5 cm, mostly in the organic form in the NTS17 and NC areas, demonstrating the contribution of the NTS to the conversion of the P reserve in the soil. The CTS treatment greatly accumulated P, especially in the inorganic form, indicating the non-conservationist characteristic of this system. The oP and iP contents in the soil were not affected by age of the NTS, which was similar to the NC. Our results show that the continuous input of organic matter deposited on the soil surface in the NTS17 increased the levels of organic and inorganic P, consequently providing greater availability of P in the soil for cultivated crops.